The effectiveness of interventions aiming to promote positive body image in adults: A systematic review - Guest, Ella; Costa, Bruna; Williamson, Heidi; Meyrick, Jane; Halliwell, Emma; Harcourt, Diana (Body image, 2019)
•Positive body image interventions improve aspects of health and well-being.•Fifteen studies, evaluating 13 interventions, were eligible for inclusion.•The two interventions for men, rated as weak, did not improve positive body image.•Strong and moderate quality interventions improved positive body image in women.•Future interventions should target multiple components of positive body image. Theory suggests promoting positive body image (PBI) through interventions would have a significant impact on health and well-being. However, little is known about the effectiveness of existing interventions. This review aimed to identify and assess the evidence of effectiveness of interventions to increase PBI in adults. Database searches were conducted using CINAHL Plus, Medline, PsychINFO, Wiley Online Library, and SCOPUS. Application of inclusion criteria and data extraction were conducted by two reviewers. Methodological quality was assessed using the Effective Public Health Practice Project Quality Assessment Tool, and narrative synthesis was conducted. Fifteen studies, evaluating 13 interventions, were included. Three studies, evaluating one online writing-based functionality intervention, were judged to have strong methodological quality and had evidence of improving body appreciation, body esteem, and functionality satisfaction. Six moderate quality studies found interventions using intuitive eating, CBT, self-compassion, and exercise improved PBI. There was limited evidence of effectiveness of interventions for men, suggesting future research is needed to better understand PBI mechanisms in men. Lack of heterogeneity of outcome measures is discussed as a limitation. Findings suggest existing interventions are effective at increasing aspects of PBI among women and support the development of interventions that target multiple components of PBI.